Metoda systemowego opisu pojęć wieloznacznych = The method of system description of ambiguous terms - Rongińska, Tatiana (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The article presents the system method of describing ambiguous terms ? the penta-basis method by W. Ganzen. It discusses theoretical assumptions of the method and possibilities to use it on the basis of four descriptive dimensions: time, space, energy and information. A dichotomous division of each dimension has been shown. The next section of this paper focuses on the attempt to analyze the concept of creativity based on the method of system description. Each dimension of the penta-basis method has been assigned with some characteristics to determine the content of creativity.
Keywords: systemowy opis; metoda pentabazy; dychotomiczny podział; czas; energia; przestrzeń; informacja; kreatywność; system description; penta-basis method; dichotomous division; time; energy; space; information; creativity